Building an Entrepreneurial Organisation - Simon Mosey; Hannah Noke; Paul Kirkham (New York Routledge, 2017)
Entrepreneurship is often focused on understanding new ventures, but the entrepreneurial flame is required in growing organisations too. This textbook examines how organisations can become more entrepreneurial to achieve sustainable growth.
Keywords: Organizational behavior; New products; Technological innovations; Diffusion of innovations; Management; Business Enterprise (BIN1071-N)